2010
DOI: 10.1183/09031936.00016309
|View full text |Cite
|
Sign up to set email alerts
|

School air quality related to dry cough, rhinitis and nasal patency in children

Abstract: Controls for indoor air quality (IAQ) in schools are not usually performed throughout Europe. The aim of this study was to assess the effects of IAQ on respiratory health of schoolchildren living in Norway, Sweden, Denmark, France and Italy.In the cross-sectional European Union-funded HESE (Health Effects of School Environment) Study, particulate matter with a 50% cut-off aerodynamic diameter of 10 mm (PM10) and CO 2 levels in a day of normal activity (full classroom) were related to wheezing, dry cough at nig… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

17
114
0
3

Year Published

2011
2011
2022
2022

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 172 publications
(138 citation statements)
references
References 26 publications
(29 reference statements)
17
114
0
3
Order By: Relevance
“…Although this effect might be smaller than other risk factors, it has a high potential for modification through simple ventilation strategies. In fact, in 90 % of the measurements in our sample, the recommended limit of 1,000 ppm (1,800 mg/m 3 ) [2] was exceeded as previously reported in schools [20], reinforcing the importance of the dissemination of better ventilation practices. Improving ventilation rates was recently associated with reduced student absences due to illness at elementary schools [13].…”
Section: Discussionsupporting
confidence: 60%
See 1 more Smart Citation
“…Although this effect might be smaller than other risk factors, it has a high potential for modification through simple ventilation strategies. In fact, in 90 % of the measurements in our sample, the recommended limit of 1,000 ppm (1,800 mg/m 3 ) [2] was exceeded as previously reported in schools [20], reinforcing the importance of the dissemination of better ventilation practices. Improving ventilation rates was recently associated with reduced student absences due to illness at elementary schools [13].…”
Section: Discussionsupporting
confidence: 60%
“…Concentration of CO 2 , temperature and relative humidity determinations were taken, as they are easy to measure and reliable indicators of indoor air contamination due to human presence (CO 2 ) and indoor comfort. The association between CO 2 concentration and respiratory illnesses in school aged children has been reported [20,7]. In addition, the Presented frequencies concern the 143 evaluated rooms.…”
Section: Discussionmentioning
confidence: 98%
“…Recently, LOGUE et al [31] , respectively. Similar concentrations were found in offices or schools [32][33][34][35]. In developing or emerging countries, compared with industrialised ones, higher indoor concentrations are often observed [3], in particular for nitrogen dioxide and PM2.5, due to differences in cooking and heating habits (see section on rural areas).…”
Section: Geographical Variations In Iaq In Industrialised Countriesmentioning
confidence: 55%
“…In a cohort of 150 asthmatic children, PM2.5 and PM2.5-10 concentrations, assessed three times every 3 months, were positively associated with the incidence rate of several respiratory symptoms, including cough, asthma symptoms and wheezing [121]. A pilot study on IAQ in a sample of schools in five European countries found that nasal patency was significantly lower in schoolchildren exposed to PM10 concentrations .50 mg?m -3 than in those exposed to concentrations ,50 mg?m -3 [34]. An increased risk of past-year asthma was found in 401 classrooms with high levels of particulate matter (OR 1.21, 95% CI 1.05-1.39) [35].…”
Section: Particulate Mattermentioning
confidence: 99%
“…Since the indoor concentration of NO 2 may be even more elevated than outdoor levels (Lee et al, 2002), there has been increased interest in recent decades in indoor NO 2 pollution, and various research programs on the health effects of indoor air quality have been developed worldwide, regarding both school (Simoni et al, 2010(Simoni et al, , 2011 and domestic (Gillespie-Bennett et al, 2011;Belanger et al, 2013) indoor environments. Children spend most of their time each day in indoor environments (Klepeis et al, 2001), and it appears that exposure to higher home indoor -and not outdoor -NO 2 levels is associated with an increased frequency of respiratory symptoms and poorer respiratory function in asthmatic children (Gillespie-Bennett et al, 2011).…”
mentioning
confidence: 99%